Drop Test of Plastic Packagings – Correlation with Material Parameters and Change of Packaging Behaviour After Impact of Standard Liquids. (23rd July 2013) - Menrad, Andreas; Goedecke, Thomas; Wagner, Manfred H.
<x xml:space="preserve">Abstract</x> A guided drop test was performed to achieve a defined and reproducible impact orientation of jerrycans. The drop heights where 50% of the jerrycans experienced a failure from a crack where fluid can escape (50% failure drop height) were compared among jerrycans made of four different materials, in their original state and preconditioned with standard liquids. To analyse the impact of only elevated temperatures, the packages were preconditioned for 21 days at 40°C without the use of chemicals. The 50% failure drop height was compared by using Young's modulus; the notched impact strength (NIS) of specimen cut from plates which were manufactured by compression moulding and the notched tensile impact strength of specimen cut‐outs of the jerrycans' side walls. The NIS depends highly on the thermal preconditioning of the plates being manufactured by compression moulding. A trend can be seen that a higher Young's modulus, a higher NIS and a higher notched tensile impact strength result in a higher 50% failure drop height, but the values are spread. The influence of the wall thickness cannot be neglected. The change of the 50% failure drop height in regard to the preconditioning at 40°C with and without nitric acid was compared in terms of their resistance to molecular degradation, density and degree of crystallinity. The conditioning at elevated temperature causes post‐crystallization. It was shown that the resistance to molecular degradation determined on pressed plates correlates with the change of the 50% failure drop height after pre‐storage with nitric acid. Copyright © 2013 John Wiley & Sons, Ltd.